A Randomized, Double-Blind, Parallel-Group Phase I Study Comparing the Pharmacokinetics, Safety, and Immunogenicity of CMAB015, a Candidate Secukinumab Biosimilar, with Its Reference Product Cosentyx® in Healthy Chinese Male Subjects - Yao F; Wang C; Ding J; Zhang Q; Zheng L; Zhang Q; Yang T; Zhang X; Shan Y; Hou S; Wang H; Zhou R; et al. (Drug Design, Development and Therapy, 2024)
Feng Yao,1,* Chenguang Wang,2,* Jie Ding,1 Qian Zhang,1 Liang Zheng,1 Qin Zhang,1 Tianshu Yang,2 Xunmin Zhang,2 Yong Shan,2 Sheng Hou,2 Hao Wang,2 Renpeng Zhou,1 Wei Hu1 1Department of Clinical Pharmacology, The Second Affiliated Hospital of Anhui Medical University, Hefei, People’s Republic of China; 2Taizhou Mabtech Pharmaceutical Co., Ltd, Taizhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wei Hu; Renpeng Zhou, Department of Clinical Pharmacology, The Second Affiliated Hospital of Anhui Medical University, No. 678 Furong Road, Hefei, Anhui, 230601, People’s Republic of China, Tel/Fax + 86 0551 65997164, Email huwei@ahmu.edu.cn; zhourenpeng@ahmu.edu.cnPurpose: Secukinumab, a monoclonal antibody targeting interleukin (IL)-17A, is approved for the treatment of psoriasis, psoriatic arthritis, ankylosing spondylitis, non-radiographic axial spondyloarthritis, enthesitis-related arthritis, and hidradenitis suppurativa. This study compared the pharmacokinetics (PK), safety, and immunogenicity of CMAB015, a candidate secukinumab biosimilar, with the reference product secukinumab (Cosentyx®) in healthy Chinese male subjects.Patients and methods: This double-blind, parallel-group study randomized healthy Chinese male subjects (N=130) to receive either a single dose of 150 mg CMAB015 or secukinumab subcutaneously. Primary study endpoints were PK parameters such as the maximum concentration (Cmax) and area under the curve from zero to infinity (AUC0-inf), while safety and immunogenicity were secondary endpoints.Results: The 90% confidence intervals (CIs) of the geometric mean ratios (GMRs) of Cmax and AUC0-inf for CMAB015 to secukinumab were all within the bioequivalence limits (80.00– 125.00%). Other PK parameters were comparable between the groups. The safety profile of CMAB015 was similar to that of secukinumab, with no serious adverse events related to treatment. The incidence of TEAEs was slightly higher in the CMAB015 group, but these events were mild to moderate in severity and did not lead to any withdrawals from the study. Immunogenicity analysis revealed low rates of anti-drug antibody (ADA) positivity, with similar rates between CMAB015 and secukinumab.Conclusion: This study demonstrated equivalent PK, comparable safety, and immunogenicity of CMAB015 to secukinumab in healthy Chinese male subjects. These findings support further clinical evaluation of CMAB015 as a secukinumab biosimilar.Trial Registration: The trial was registered on Clinicaltrials.gov (Identifier No. NCT05734482) and Chinadrugtrials.org.cn (Identifier No. CTR20230105).Keywords: CMAB015, secukinumab, biosimilar, pharmacokinetics, safety, immunogenicity